America's book: the rise and decline of a Bible civilization, 1794-1911 - Noll, Mark A. (Oxford scholarship online, 2022)
"This book shows how the Bible decisively shaped American national history even as that history decisively influenced the use of Scripture. It explores the rise of a strongly Protestant Bible civilization in the early United States that was then fractured by debates over slavery, contested by growing numbers of non-Protestant Americans (Catholics, Jews, agnostics), and torn apart by the Civil War. Scripture survived as a significant, though fragmented, force in the more religiously plural period from Reconstruction to the early twentieth century. Throughout, the book pays special attention to how the same Bible shone as hope for black Americans while supporting other Americans who justified white supremacy"--